Teacher Participation in Professional Learning Programs in Classroom Behavior Management - Pramesti Pradna Paramita; Fitri Andriani; Muryantinah Mulyo Handayani; Rusdi Rusli (Jurnal Prima Edukasia, 2023)
Professional learning can help teachers to develop their knowledge and abilities to support their functions and roles as educators. However, studies show that most teachers in Indonesia have not been involved in continuing professional development. This study aims to describe the professional learning program that has been attended by elementary school teachers in Indonesia regarding classroom behavior management. The results of this study indicate that only some of the teacher participants stated that they had participated in a professional learning program on managing student behavior in the classroom. Organizers of the professional learning programs attended by teachers include the Ministry of Education, Culture, Research, and Technology, schools, universities, and other community members. Participants also shared about the benefits of these activities in managing student behavior in the classroom. The results of this study suggest the importance of implementing more professional learning programs that focus on managing student behavior in the classroom, which are designed effectively to have a direct impact on behavior management practices carried out by teachers in the classroom